Evaluation of the pneumatic tube system for transportation of packed red cell units - Supriya Dhar (Asian Journal of Transfusion Science, 2015)
Background: Pneumatic tube system (PTS) is commonly used in hospital settings to transport blood samples to diagnostic laboratories. At our blood center, we receive blood requisitions via the PTS, but units are carried to the ward by human courier. Recently we considered using the PTS for transporting blood units. Since, there are reports of hemolysis in blood samples sent through the PTS, we evaluated this system for transporting red cell units. Aims: The aim was to assess the effect of PTS transport on the quality of packed red cell units. Materials and Methods: A total of 50 red blood cells units (RBC), (25 non-irradiated and 25 irradiated) were subjected to transportation through the PTS. The control arm in the study was age-matched RBC units not subjected to PTS transport. Each RBC unit was evaluated for hemoglobin (Hb), lactate dehydrogenase, potassium and plasma hemoglobin (Hb). The paired t-test was used to compare these parameters, and the P value was calculated. Results and Conclusion: The percentage of hemolysis after transportation through PTS was below the recommended guidelines. Delivery of the blood unit to the wrong station, bags lying unattended at the destination were few of the problems that had to be addressed. To conclude, though the PTS is a safe means of transporting blood products with reduction in the turn-around-time, it must be validated before use.